Subpolar Southern Ocean response to changes in the surface momentum, heat, and freshwater fluxes under 2xCO2 - Boeira Dias, FB; Domingues, CM; Marsland, SJ; Stephen Rintoul; Uotila, P; Fiedler, R; Mata, MM; Nathaniel Bindoff; Abhishek Savita (2021)
The Antarctic subpolar Southern Ocean (sSO) has fundamental climate importance. Antarctic Bottom Water (AABW) originates in the sSO and supplies the lower limb of the meridional overturning circulation (MOC), occupying 36% of ocean volume. Climate models struggle to represent continental shelf processes that form AABW. We explore sources of persistent model biases by examining response of the sSO to perturbations in surface forcing in a global ocean–sea ice model (ACCESS-OM2) that forms AABW both on shelf and in open ocean. The sSO response to individual and combined perturbations of surface heat, freshwater, and momentum fluxes follows the WCRP CMIP6 FAFMIP-protocol. Wind perturbation (i.e., a poleward shift and intensification of the westerlies) is dominant, enhancing AABW formation and accelerating the global MOC. This occurs through upwelling of warm waters and inhibition of sea ice growth during winter, which triggers large open water polynya (OWP) events with associated deep convection. These events occur in the Weddell and Ross Seas and their variability is associated with availability of heat at midocean depths. These OWPs cease when the heat reservoir is depleted. Effects of surface warming and freshening only partially compensate changes from increasing winds on ocean stratification and depletion of AABW formation. These results indicate that overly convective models, such ACCESS-OM2, can respond to CO 2 -perturbed scenarios by forming too much AABW in OWP, which might not hold in models without OWPs. This might contribute to the large intermodel spread thermosteric sea level projections, being relevant to the interpretation of future projections by current climate models.